1998
DOI: 10.1007/bf02495592
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of alkaline hydrolysis of esters of phosphorus acids in micellar and hexagonal phases in the cetyldimethylethylammonium bromide—NaOH—water system

Abstract: The influence of micellar (Mi) and hexagonal (E) mesophases of the cetyldimethylethylammonium bromide--NaOH--water system (I) on the rates of alkaline hydrolysis of, and O,O-di~-nitrophcnyl)methyl phosphonate (4) was studied by UV spectrophotomerry. The binding constants of the substrates, critical mieelle concentrations, and rate constants of reactions in the micellar phase were determined, in micellar solutions of system I, a tenfold increase in the rates of alkaline hydrolysis of 2--4 was observed. An incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…Functionalized micelles containing a bound nucleophile accelerate reactions at acyl or phosphoryl groups. [74,[86][87][88][89][90][91][92][93][94][95][96] In general, cationic micelles accelerate the reaction of neutral substrates with anionic reactants, for example, hydroxide ions, [46,[97][98][99][100][101] oximate ions, [84,86,[102][103][104] fluoride ions, [83] or thiolate ions. [105] Miller et al [100] found that the main causes for the 16.5-fold increase in the reaction rate of the basic hydrolysis of homologous nitrophenyl esters of carboxylic acids in latices functionalized with quaternary ammonium groups was a 90 000-fold increase in substrate concentration and a 10-fold increase in the hydroxide ion concentration.…”
Section: Solvolyses and Metalloenzyme Modelsmentioning
confidence: 99%
“…Functionalized micelles containing a bound nucleophile accelerate reactions at acyl or phosphoryl groups. [74,[86][87][88][89][90][91][92][93][94][95][96] In general, cationic micelles accelerate the reaction of neutral substrates with anionic reactants, for example, hydroxide ions, [46,[97][98][99][100][101] oximate ions, [84,86,[102][103][104] fluoride ions, [83] or thiolate ions. [105] Miller et al [100] found that the main causes for the 16.5-fold increase in the reaction rate of the basic hydrolysis of homologous nitrophenyl esters of carboxylic acids in latices functionalized with quaternary ammonium groups was a 90 000-fold increase in substrate concentration and a 10-fold increase in the hydroxide ion concentration.…”
Section: Solvolyses and Metalloenzyme Modelsmentioning
confidence: 99%
“…Kationische Micellen beschleunigen in der Regel Reaktionen neutraler Substrate mit anionischen Reaktanten, z. B. Hydroxidionen,46, 97101 Oximationen,84, 86, 102104 Fluoridionen83 oder Thiolationen 105. So fanden Miller et al100 für die basische Hydrolyse von homologen Alkansäurenitrophenylestern in mit quartären Ammoniumgruppen funktionalisierten Latices, dass wesentliche Ursachen für die bis zu 16.5fach erhöhten Reaktionsgeschwindigkeiten eine um den Faktor 90 000 erhöhte Konzentration des Substrats und eine 10fach erhöhte Hydroxidionenkonzentration sind.…”
Section: Reaktionen In Micellenunclassified
“…One of the most important processes leading to micellar effects on the reactions is the solubilization of the TNT in the micellar interiors, where most reaction were considered to occur, and this could lead to the increase in local concentration of reactants and then affect the reaction rate of TNT hydrolysis. [18] Bakeeva et.al [19] have reported that OH À ions, which are reagents in the hydrolysis reaction of ester, are concentrated in micelles (due to Coulomb forces) in the region of positively charged alkyl ammonium groups, that is, in the Stern layer in micelles. The site of localization of substrates in supramolecular associates depends on their structure, and the local micro environments of hydrophilic and hydrophobic groups of the substrate can be different.…”
Section: Alkaline Hydrolysis Of Tnt In the Micellar Solutionsmentioning
confidence: 98%